Transformações para a sustentabilidade energética : modelo UniTS-Energy para avaliação em universidades - Salvia, Amanda Lange (2020)
The role of universities in promoting sustainability is internationally recognized and assessed by several tools. This assessment may have different approaches, considering the main aspects of the institutions, but it usually tends to present a holistic view of sustainability and not to deepen into certain elements, such as energy. In this sense, Sustainable Development Goal 7 (SDG 7) reinforces the importance of the theme of Accessible and Clean Energy and the role of the university in combining energy sustainability with its organizational and knowledge transmission processes. The aim of this research was to propose a model of transformations to energy sustainability at universities, assessing their performance and contributions to sustainable development. The methodology consisted of three phases. The first phase (development of the model itself) had three stages, each one providing subsidies to assemble its components: content analysis in sustainability assessment tools in universities; case study at a foreign university; and international exploratory study. The model was then validated in a focus group with experts in the field of sustainability and applied at a Brazilian university to assess it in relation to its current stage of transformation to sustainability in energy, in addition to the possibility of communicating its progress in relation to to the ideal situation and formalize its contribution to sustainable development. The Model of Transformation for Energy Sustainability in Universities - UniTS-Energy consists of 4 transformation stages (Inertia, Beginner, Intermediate and Advanced) and has 18 evaluation elements, distributed among the four main areas of activity of universities (teaching, operations , research and extension) and an additional area focused on external support and SDG 7. Each element has a transformation scale between the stages and an associated score; the final result is obtained through the weighted average of all the elements and provides the university's final framework in UniTS-Energy. The application of the model for diagnosing the current transformation situation for energy sustainability of the selected Brazilian university - University of Passo Fundo, pointed out challenges and potentialities. As challenges, the access to necessary information, segregation of sectors and the importance of having a multisectoral work team, in addition to the need for increased communication with the academic community and its involvement in sustainability issues. As potentialities, the development of a sustainability/green office, greater engagement with local communities and with the Sustainable Development Goals, and exploration of online teaching modules focused on sustainability. UniTS-Energy has the differential of evaluating sustainability in the context of transformation and exclusively in the field of energy, being a useful tool to guide efforts in the search for energy sustainability in all areas of the institution's operations, in addition to including SDG 7 in its assessment.